The International Conference on Islam and Development in Southeast Asia - Omar Altalib (International Institute of Islamic Thought, 1991)
The International Conference on Islam and Development in Southeast Asia was held during September 25-26, 1991, at the Equatorial Hotel, Kuala Lumpur, Malaysia. The conference was jointly organized by the Academy of Malay Studies (University of Malaya), the Islamic Academy (University of Malaya), and the Information and Resource Center (Singapore) and was sponsored by the Hanns-Seidel Foundation. The conference's stated aim was to demonstrate the differences in programs for cooperation between Islamic countries, the integration attempts of developing countries, and the actual economic and political situations of Southeast Asian countries. There were four main panels in the program: a) Islam and Development in Southeast Asia: A Historical Perspective; b) Islam and the Political Process; c) Islam and Economic Development; and 4) Islam and the Future of the Region. In the first panel, Khoo Kay Kim (professor of Malaysian history, University of Malaya) pointed out that Muslims have historically emphasized education, while in modern times they have tended to allow education to be shaped by outside rather than inside influences. In addition, Muslim education in Southeast Asia has lagged behind national development. At present, the education system in Malaysia continues to produce students who ...